Individual employment effects of job creation schemes in Germany with respect to sectoral heterogeneity - Marco Caliendo; Reinhard Hujer; Stephan L. Thomsen (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2005)
Job creation schemes (JCS) have been one important programme of active labour market policy (ALMP) in Germany for a long time. They aim at the re-integration of hard-to-place unemployed into regular employment. A thorough microeconometric evaluation of these programmes was hindered by the fact, that the available (survey) datasets have been too small to account for a possible occurrence of effect heterogeneity. However, identifying effect heterogeneity can help to improve the design and implementation of future programmes. Hence, we use an administrative dataset of the Federal Employment Agency, containing over 11,000 participants to analyse the employment effects of JCS on an individual level. Whereas in a previous paper we analysed these effects with respect to group-specific and regional heterogeneity, we focus here explicitly on effect heterogeneity caused by differences in the implementation of programmes. In particular, we first evaluate the effects with respect to the economic sector in which the JCS are accomplished. Second, we analyse if different types of promotion lead to different effects. And finally we examine if there are varying effects which can be attributed to different implementing institutions. The results are rather discouraging and show that JCS are in general not able to improve the re-integration chances of participants into regular employment.
Keywords: H43; J68; C13; 330; IAB-Bewerberangebotsdatei; IAB-Maßnahmeteilnehmergrunddatei; Arbeitsbeschaffungsmaßnahme - Erfolgskontrolle; Wirkungsforschung; Wirtschaftszweige; Trägerschaft; berufliche Reintegration; Teilnehmer; beruflicher Verbleib; Geschlechterverteilung; Westdeutschland; Ostdeutschland; Bundesrepublik Deutschland